2020
DOI: 10.1021/acs.inorgchem.0c02035
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Correlation between Oxide Ion Mobility and Site Distributions in Ba3NbWO8.5

Abstract: A correlation between oxygen site distributions and ionic conductivity has been established in the recently discovered family of oxide-ion conductors Ba3M2O8.5±δ (M = Nb, V, Mo, W). We rationalise this observation on the basis of structural insights gained from the first single-crystal neutron diffraction data collected for a member of this family, Ba3NbWO8.5, and theoretical considerations of bonding and O site energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…The structural parameters refined by the Rietveld analysis of neutron-powder-diffraction data of Ba 3 WNbO 8.5 in this work agree well with those from single-crystal neutron diffraction experiments in the literature. 45,59 Thus, there is no influence of the impurity phase and surface absorption on the structural parameters in our polycrystalline samples.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The structural parameters refined by the Rietveld analysis of neutron-powder-diffraction data of Ba 3 WNbO 8.5 in this work agree well with those from single-crystal neutron diffraction experiments in the literature. 45,59 Thus, there is no influence of the impurity phase and surface absorption on the structural parameters in our polycrystalline samples.…”
Section: Resultsmentioning
confidence: 88%
“…The present split-atom model with the 6c W,Nb2 and 18h O3 sites is consistent with the single-crystal X-ray, single-crystal, and powder neutron diffraction analyses in the literature. 37,45,58 Total neutron scattering studies demonstrated the possibility of the presence of five-fold (Mo,Nb)O 5 polyhedra in Ba 3 MoNbO 8.5−δ . 59 Here, we have shown the large spatial distribution of the O3 atom through the split-atom models also in Ba 3 MoNbO 8.5−δ , 18 which is consistent with the presence of the five-fold (Mo,Nb)O 5 polyhedra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Moving instead from BNMO to BNWO, E1 increases dramatically, likely because of the lower fraction of tetrahedral units. In this respect, Auckett et al 48 suggested that it is the energy difference between the two O sites that drive the occupancies observed experimentally, not the opposite. Gilane et al applied BVEL to Ba 3 VWO 8.5 (BVWO), which exhibits ordered vacancies on the B2 site.…”
Section: Layered Perovskitesmentioning
confidence: 99%
“…We note that both Mo 6+ and W 6+ dopants introduce the same number of interstitial O 2À ions, yet the conductivity enhancement is observed to be greater in Mo 6+ -doped LaNbO 4 ; this is perhaps related to a stronger trapping effect near the W 6+ dopant ions (which our BVEL analysis does not quantify) or to the greater tendency for Mo 6+ to tolerate a variety of coordination geometries and low coordination numbers than W 6+ , 65 which has been identied as a factor contributing to the superior oxide-ionic conductivity of Mo-based analogues of other conductive oxides. 66 A further consequence of the above nding is that the enhancement of oxide-ionic conductivity in Mo 6+ -doped LaNbO 4 is likely to reach an upper limit when the concentration of oxide-trapping dopant cations becomes high enough to disrupt a signicant proportion of conduction pathways in the material. The close similarity of the conductivity data recorded for LNMO16 and LNMO20 (Fig.…”
Section: Conductivity Mechanisms In Lnmomentioning
confidence: 99%